Coronavirus Disease 2019–Associated Thrombosis and Coagulopathy: Review of the Pathophysiological Characteristics and Implications for Antithrombotic Management - Ortega‐Paz, Luis; Capodanno, Davide; Montalescot, Gilles; Angiolillo, Dominick J. (Journal of the American Heart Association, 2021)
Coronavirus disease 2019 (COVID‐19) is an infectious disease caused by severe acute respiratory syndrome coronavirus‐2, which has posed a significant threat to global health. Although the infection is frequently asymptomatic or associated with mild symptoms, in a small proportion of patients it can produce an intense inflammatory and prothrombotic state that can lead to acute respiratory distress syndrome, multiple organ failure, and death. Angiotensin‐converting enzyme 2, highly expressed in the respiratory system, has been identified as a functional receptor for severe acute respiratory syndrome coronavirus‐2. Notably, angiotensin‐converting enzyme 2 is also expressed in the cardiovascular system, and there are multiple cardiovascular implications of COVID‐19. Cardiovascular risk factors and cardiovascular disease have been associated with severe manifestations and poor prognosis in patients with COVID‐19. More important, patients with COVID‐19 may have thrombotic and coagulation abnormalities, promoting a hypercoagulable state and resulting in an increased rate of thrombotic and thromboembolic events. This review will describe the pathophysiological characteristics of the cardiovascular involvement following infection by severe acute respiratory syndrome coronavirus‐2, with a focus on thrombotic and thromboembolic manifestations and implications for antithrombotic management.